2017
DOI: 10.3390/diagnostics7020027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Direct Sequencing, Real-Time PCR-High Resolution Melt (PCR-HRM) and PCR-Restriction Fragment Length Polymorphism (PCR-RFLP) Analysis for Genotyping of Common Thiopurine Intolerant Variant Alleles NUDT15 c.415C>T and TPMT c.719A>G (TPMT*3C)

Abstract: Thiopurine intolerance and treatment-related toxicity, such as fatal myelosuppression, is related to non-function genetic variants encoding thiopurine S-methyltransferase (TPMT) and Nudix hydrolase 15 (NUDT15). Genetic testing of the common variants NUDT15:NM_018283.2:c.415C>T (Arg139Cys, dbSNP rs116855232 T allele) and TPMT: NM_000367.4:c.719A>G (TPMT*3C, dbSNP rs1142345 G allele) in East Asians including Chinese can potentially prevent treatment-related complications. Two complementary genotyping approaches,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…At the same time, studies which used other methods (mainly PCR‐RFLP) than Taqman assays or sequencing assays as genotype detection had significant association between the risk alleles (rs266729 in ADIPOQ and rs2144908 in HNF4A) and T2D. Sequencing has been regarded as “golden standard” in sequence variations determination, while in this study, none of five studies using sequencing assays has significant association between G allele of rs266729 and T2D.…”
Section: Discussionmentioning
confidence: 57%
“…At the same time, studies which used other methods (mainly PCR‐RFLP) than Taqman assays or sequencing assays as genotype detection had significant association between the risk alleles (rs266729 in ADIPOQ and rs2144908 in HNF4A) and T2D. Sequencing has been regarded as “golden standard” in sequence variations determination, while in this study, none of five studies using sequencing assays has significant association between G allele of rs266729 and T2D.…”
Section: Discussionmentioning
confidence: 57%
“…3C allele to be most common in the Asian population[1]. Studies in Nigeria and Libya have shown majority of the African population to have the *3C allele, a finding supported in a study on TPMT activity in African-Americans byHon et al (1999) [8,51,52].…”
mentioning
confidence: 72%
“…Thiopurine methyltransferase is encoded by the TPMT gene which is located on chromosome 6 [1]. This gene exhibits an autosomal codominant genetic polymorphism which can lead to an absent or low level of TPMT activity in individuals who are heterozygous or homozygous for this genetic polymorphism [8].…”
Section: Thiopurine Methyltransferase and Azamentioning
confidence: 99%
See 2 more Smart Citations